Cognitive decline in older adults with epilepsy: The Cardiovascular Health Study. (23rd November 2020) - Choi, Hyunmi; Thacker, Evan L.; Longstreth, William T.; Elkind, Mitchell S. V.; Boehme, Amelia K.
Abstract: Objective: Cognitive decline is a major concern for older adults with epilepsy. Whether and how much faster older adults with epilepsy experience cognitive decline beyond expected age‐related cognitive change remain unclear. We sought to estimate and compare rates of cognitive decline in older adults with and without epilepsy. Methods: The Cardiovascular Health Study is a population‐based longitudinal cohort study of 5888 US adults aged 65+. Cognitive function was assessed annually with Modified Mini‐Mental State Exam (3MS) and Digit Symbol Substitution Test (DSST). We used linear mixed models to estimate average rates of decline in 3MS and DSST scores by epilepsy status (prevalent, incident, or no epilepsy), adjusted for risk factors associated with cognitive decline. Results: The rate of decline in 3MS was significantly faster in prevalent epilepsy ( P < .001) and after incident epilepsy ( P = .002) compared with no epilepsy. Prevalent epilepsy and apolipoprotein E gene ( APOE ) ε4 (ApoE4) had a synergistic interaction, whereby prevalent epilepsy and ApoE4 together were associated with 1.51 points faster annual decline in 3MS than would be expected if prevalent epilepsy and ApoE4 did not interact ( P < .001). Older adults with prevalent epilepsy had a significantly lower initial DSST score and faster rate of decline compared to those with no epilepsy ( P < .001). Significance: Faster decline in global cognitive ability seen in this study validates concerns of patients. ApoE4 allele status was an effect modifier of the relationship between cognitive decline and prevalent epilepsy. Further research is warranted to explore biological mechanisms and possible interventions to mitigate cognitive decline.